Role of Shadow Teacher in the provision of Academic and Social Support for Children with Special Needs at Inclusive Schools - Abdul Hamid (JIE, 2020)
The role of a shadow teacher is to help the children needing to support activities by helping fill in the Gaps in the learning procedure and overall assist the child to create academic and social abilities. Quantitative research design was used and the study was descriptive in nature. Cross-sectional survey method was used. Sample of 186 shadow teachers selected through random samplingtechnique from Lahore, Gujranwala, Islamabad and Faisalabad cities of Pakistan.